Application of perennial sweet pea in soil and water conservation - Shi, Lin; Dai, Chenyang; Maruthaveeran, Sreetheran (Multidisciplinary Digital Publishing Institute, 2023)
To address the issue of soil erosion and limited economically valuable vegetation resources, perennial sweet peas were introduced to Hebei Province, China, and showed favorable biological attributes. Nevertheless, its specific efficacy within soil and water conservation endeavors requires further examination. This study selected four trial sites within Hebei Province to assess four-year-old perennial sweet peas’ soil and water conservation functionality. The findings underscored that cultivating perennial sweet pea plots on 9° disturbed slopes notably outperformed bare ground (CK) in their rainwater absorption capacity. Specifically, in the 0–20 cm soil layer, moisture increased from 10.51% to 17.39%, in the 20–40 cm layer from 10.63% to 17.25%, and in the 40–60 cm layer from 10.09% to 16.04%. The dense canopy formed by perennial sweet peas effectively intercepted 25–32% of precipitation. Fallen organic matter also demonstrated commendable water absorption features. During severe rain, the perennial sweet pea showcased a 90.4% runoff reduction and a notable sediment interception. Their deep and well-developed root system enhanced soil structure and infiltration. The outcomes of this study highlight the perennial sweet peas’ potential in soil erosion mitigation, rainwater retention, and soil improvement, which carries substantial implications for sustainable land management and ecosystem restoration initiatives. Furthermore, the successful introduction of perennial sweet peas could serve as a model for analogous ecological interventions in regions confronting similar challenges, offering holistic solutions to soil and water conservation in environmentally sensitive areas.